Semi-specific intron-exon splice junction markers in bryophyte studies - Sawicki, Jakub; Szczecińska, Monika (Biodiversity: Research and Conservation, 2007)
We present a protocol for use of intron-exon splice junction (ISJ) markers in studies on bryophytes. The advantages and disadvantages of the method are discussed and compared with other PCR-based markers like AFLP, ISSR and RAPD.